A prospective study of thyroid profile in children aged 1 month to 12 years of age with newly diagnosed seizure disorder started on first line antiepileptic drugs - M., Santhosh Kumar; Pinnamaneni, Supraja; C., Anitha (International Journal of Contemporary Pediatrics, 2023)
Background: The study's primary aim was to determine the variation in the thyroid profile status in children with newly diagnosed seizure disorders started on first-line antiepileptic drugs. In addition, this study compares the incidence of hypothyroidism secondary to phenytoin, phenobarbitone, valproate and carbamazepine. Methods: A total of 60 children with newly diagnosed seizure disorders belonging to the age group of 1 month to 12 years were enrolled in the study. The children were subjected to a detailed history and neurological examination, and serum levels of T3, T4, and thyroid-stimulating hormone (TSH) were tested. Results: In this study, out of 60 children, the clinical signs and symptoms of hypothyroidism were present only in one subject (1.7%), and the remaining 59 had no signs and symptoms of hypothyroidism. The mean TSH value increased from baseline 1.62±1.17 to 3 months 2.2±1.38 and 6 months 2.78±149 (p value<0.05%). The incidence of subclinical hypothyroidism among the phenytoin group (n=33) was 6.06%. Among the sodium valproate group (n=23), the incidence was 8.6%, and among the carbamazepine group (n=4), the incidence was 25%. Conclusions: Antiepileptic drugs can alter thyroid function tests. In this study, there was no overt hypothyroidism noted. But subclinical hypothyroidism was reported in subjects using phenytoin, valproate and carbamazepine.